A new species of Sogatella (Hemiptera: Delphacidae) from temperate Argentina - Mariani,Roxana (2018)
ABSTRACT A new species from Argentina, Sogatella unidentata sp. nov. (Hemiptera: Delphacidae), is described and illustrated as belonging to the Sogatella furcifera group. The main distinctive characteristics are tegmen coloration, shape of aedeagus and number and dispositions of its teeth, and shape of parameres in males; length of the ovipositor, and shape of the gonapophysis IX in females. A key is included to facilitate the comparison of the new species with the closely allied. Furthermore, information on host plants and geographical distribution is provided. This is the southernmost record in the distribution of the S. furcifera group.